Analisis Faktor Produksi dan Perilaku Risiko Petani pada Usahatani Padi Sawah dengan Sistem Tanam Jajar Legowo - Rezki Putra (PT Hakhara Akademia Indonesia, 2025)
This study aims to analyze the influence of production factors on lowland rice production as well as farmers’ behavior toward production risk in the implementation of the jajar legowo planting method in Empat Balai Village, Kampar Regency. The research was conducted using a survey method involving 71 rice farmers who are members of two farmer groups actively applying the jajar legowo method, namely the Pulai Makmur and Manggadi Farmer Groups. The data consisted of primary and secondary data obtained through direct interviews with farmers. Data analysis was carried out using the Cobb–Douglas production function transformed into a natural logarithmic form, along with risk behavior analysis using the Moscardi and de Janvry model. The results show that, simultaneously, the production factors of seed, fertilizer, pesticide, and labor have a significant effect on lowland rice production under the jajar legowo method. Partially, seed, fertilizer, and pesticide variables have a positive and significant effect on rice production, while labor does not have a significant effect. The Adjusted R² value of 0.686 indicates that the model explains 68.6 percent of the variation in rice production. The risk behavior analysis reveals that the majority of rice farmers are risk-averse, accounting for 76.1 percent of the respondents, while the remainder are risk-neutral.